Using Food Composition Tables to Estimate Decreases in Sodium Intake Due to the Reformulation of Packaged and Ultra-Processed Foods in a Young Population in South Africa - Alexandra Ross; Elizabeth C Swart; Joelaine Chetty; Malory Jumat; Tamryn Frank; Averalda van Graan (Public Health Nutrition)
Abstract